Micellar Catalysed Oxidative Decarboxylation of Butyric and Iso-Butyric Acids by Acidine Permanganate Ions - Pare, Brijesh; Bhagwat, V.W.; Shastry, V.R. (Asian Journal of Chemistry, 2010)
A.micellar catalyzed oxidative decarboxylation of butyric and isobutyric acid by permanganate ion in moderately concentrated acidic medium has been studied. The premicellar kinetics has been rationalised in the light of pseudo-phase model. The positive cooperativity index (n = 2.09) has been computed. The decarboxy-lation reactions are acid catalysed and, therefore, various hypotheses for the mechanism of acid catalysis were tested. Thus, the role of water molecule as proton abstracting agent is established. On addition of fluoride ions, a known complexing agent, there is a decrease in the reaction rate. The effects of variation of ionic strength and thermodynamic parameters have been computed. The stoichiometry for the reaction is: 5CH3CH2CH2COOH + 2MnO4- + 6H+→ 5CH3CH2CH2OH + 3H2O + 5CO2 + 2Mn2+ On the basis of the various observations and product characterization a most plausible mechanism has been envisaged.